Participation motives in outdoor physical activities at Taman Rakyat Klang, Selangor / Siti Wafiqah Mohd Nor … [et al.] - Mohd Nor, Siti Wafiqah; Mohd Sidi, M. Adli; Isa, Kalam Azad; Azam, Zulkhairi (Universiti Teknologi MARA, Pahang, 2022)
Motivation factors which include intrinsic motivation and extrinsic motivation play a vital role in getting people to engage in outdoor physical activities. Recreational parks become an attraction spot for exercise, leisure, and recreational activities as it could provide the best experience. A person’s attitude towards exercise is thought to be a contributing factor to physical inactivity. This study aimed to compare between the intrinsic and extrinsic motivation for the different genders’ participation in outdoor physical activities at Taman Rakyat, in Klang, Selangor (TRKS). A quantitative survey was conducted using self-administered questionnaire and distributed to the active visitors (n=300). The motivation components discussed included the intrinsic motivation and extrinsic motivation. The data collected were statistically analysed using Mann-Whitney Test to compare the two factors. Overall, the results indicated that the visitors at TRKS were significantly motivated to participate in outdoor physical activities due to the intrinsic motivation which are associated with fun, interest and enjoyment. Male respondents were significantly motivated by intrinsic motivation whereas female respondents were significantly motivated by extrinsic motivation. The findings provide valuable information on outdoor recreation parks for future service planning and development.